Discovery of the genus Micropeneta Pic in China, with description of a new species (Coleoptera: Tenebrionidae: Gnathidiini) - Li, Bo-Yan; Jiang, Ri-Xin (Zootaxa, 2019)
The tenebrionid genus Micropeneta, Pic 1921 is recorded from China for the first time. A new species, Micropeneta qilin Li & Jiang sp. n., is described, figured and compared with its congeners. Habitat information and collection data of the new species are given.